Selection of working frequency bands of mine-used radio systems and equipments - SUN Ji-ping; WU Yun-xia (Gong-kuang zidonghua, 2013)
The paper put forward that mine-used radio systems and equipments are strictly prohibited using frequencies of broadcast, TV, radio astronomy, safety relief, radio navigation, and gave strictly prohibited frequency bands. It put forward that mine-used radio systems and equipments should select amateur band firstly, such as industrial, scientific and medical equipment frequency bands, and gave recommended frequency bands. It proposed that mine-used radio systems and equipments should choose consistent or similar to ground frequency band when business of mine-used radio systems and equipments is conformity or similar to ground business, and gave frequency bands of the similar business. It also gave the in use frequency bands in coal mine underground.